2007
DOI: 10.1007/s00414-007-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of miniY-STR multiplex PCR systems for extended 16 Y-STR loci

Abstract: We developed three short amplicon Y-chromosomal short tandem repeat (miniY-STR) polymerase chain reaction multiplex systems for 16 Y-STR loci (DYS441, DYS446, DYS462, DYS481, DYS485, DYS495, DYS505, DYS510, DYS511, DYS549, DYS 575, DYS578, DYS593, DYS618, DYS638, and DYS643), using newly designed primer sets. In an assay of 238 Japanese males using the three miniY-STR systems, amplification product lengths ranged from 91 to 151 bp for all 16 Y-STR loci. We identified 212 different haplotypes among the 238 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Although such kits are not developed specifically to analyze degraded samples of DNA, they are commonly used for this purpose. However, the results are not so satisfactory, as the products' amplification varies between 100 and 450 bp and in general, amplification of this type of DNA is hampered with STRs that amplify fragments over 200bp [8]. In this study, results obtained from amplifications using AmpFLSTR ® Identifiler™ and AmpFlSTR ® Yfiler™ commercial kits, both with STR Kits confirm that.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although such kits are not developed specifically to analyze degraded samples of DNA, they are commonly used for this purpose. However, the results are not so satisfactory, as the products' amplification varies between 100 and 450 bp and in general, amplification of this type of DNA is hampered with STRs that amplify fragments over 200bp [8]. In this study, results obtained from amplifications using AmpFLSTR ® Identifiler™ and AmpFlSTR ® Yfiler™ commercial kits, both with STR Kits confirm that.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, results obtained from amplifications using AmpFLSTR ® Identifiler™ and AmpFlSTR ® Yfiler™ commercial kits, both with STR Kits confirm that. It has been demonstrated that miniSTRs are a better method for analyzing degraded DNA [1,2,7,8]. Results obtained here were more efficient when using the AmpFLSTR ® Minifiler™ commercial kit and the multiplex Mini YSTR09, both containing mini-YSTR.…”
Section: Discussionmentioning
confidence: 63%
“…To improve the usefulness of the systems for analyzing degraded DNA samples, we designed primers to render amplicons of 150 bp or shorter. This stems from the fact that past research has already shown that DNA fragmentation is a major obstacle in analyzing degraded DNA samples, and because in STR analysis, we obtained extremely useful results with amplicons 150 bp or smaller . In the assay of the Jomon skeleton, c .260 bp region in the HVS1 failed to be amplified.…”
Section: Resultsmentioning
confidence: 91%
“…To our knowledge, there are no published data about the genetic structure of Y-chromosome in Kerala population, although data on various other ethnic groups have been reported in the last decade (12-19). Y-STR haplotypes are useful for investigating and reconstructing the phylogeny of the more recently diverged paternal lineages (5,6), as well as for forensic/paternity testing (20-24).…”
Section: Discussionmentioning
confidence: 99%